Phthalocyanine-aniline dyad constructed with click electrochemistry: a novel hybrid electrochromic material - KOCA, ATIF (SPRINGER, 2020)
A novel hybrid electrochromic material, dyad of poly 4-azidoaniline (PANI-N-3) and manganese phthalocyanine bearing terminal alkynyl moieties (TA-MnPc), was firstly prepared as an electrochromic anode (ITO/PANI-N-3-TA-MnPc). ITO/PANI-N-3-TA-MnPc was developed to improve the coloration efficiency, switching time, cycle live, and the viability of the phthalocyanine and aniline for the electrochromic applications. Click electrochemistry reaction (CEC) was employed for the binding of TA-MnPc to the electropolymerized PANI-N-3 film on the ITO electrode. Characterization of the constructed electrode was performed with square wave voltammetry (SWV), infra-red spectroscopy (IR), scanning electron microscopy (SEM), and 4-probe conductometer, and then it was tested as a potential electrochromic material. PANI-N-3-TA-MnPc hybrid chromophore provided extraordinary electrochromic responses with improved coloration efficiency, faster switching times, and long cycle live. Color change between green and brown with faster switching times (0.50 s) and longer cycle live (no optical lose with 300 CA cycles) made this hybrid material a possible building blocks for advanced electrochromic devices needing green-brown color change with high optical contrasts and faster response times.
Keywords: Electrochromic polymers; materials; Click electrochemistry; 4-Azidoaniline; Manganese phthalocyanine; Hybrid materials; LANGMUIR-BLODGETT-FILMS; THIN-FILMS; MANGANESE PHTHALOCYANINE; POLYANILINE; COMPOSITE; METALLOPHTHALOCYANINES; ABSORPTION; COLORATION; ELECTRODES; SENSOR